Features of postoperative pain management in patients with maxillofacial pathology O. Tymofieiev, - Тимофеев, Алексей Александрович; Ушко, Наталия Алексеевна; Максимча, Сергей Васильевич; Ухарская, Оксана Анатольевна; Блинова, Виктория Павловна; Серга, Елена Александровна; Ушко, Виктор Дмитриевич (Actual Dentistry, 2019)
Purpose: to give a comparative description of the non-narcotic analgesics use as a step-down analgesic therapy to eliminate the post-traumatic pain in the patients with maxillofacial pathology. Methods. 229 patients with maxillofacial pathology. Results. Ketorolac and dexketoprophenum are effective and safe drugs for treatment of pain in the patients with maxillofacial pathology. ketorolac is a non-steroidal non-narcotic analgesics that has the strongest and prolonged analgesic effect, having the least number of side effects as well. Conclusions. Ketorolac has the strongest and prolonged analgesic action and we recommend it for use in patients with maxillofacial pathology. Key words: ketorolac, dexketoprophenum, analgesics, analgesia, step-down therapy, pain, maxillofacial pathology.